2018
DOI: 10.1002/ejic.201800019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Stable Gold(III) PNP Pincer Complexes

Abstract: The first mononuclear Au III PNP pincer complexes [PNP = bis(2-diisopropylphosphinophenyl)amide] are reported. The chloro complex [(PNP)Au(Cl)][OAc F ] (OAc F = OCOCF 3 ) was synthesized by microwave irradiation of a tetrachloroaurate salt and the neutral PNHP ligand. Dehalogenation with AgOAc F afforded the trifluoroacetate-bound complex [(PNP)Au(OAc F )]-[OAc F ]. Both complexes were characterized by NMR spectroscopy and X-ray crystallography. Electronic absorption spectro-[a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Gold(III)-complexing ligands offering a phosphine coordination site along with an additional heteroatomic electron donor Received: September 11, 2020 Published: November 10, 2020 41 II, 42 III, 42 IV, 43,44 V, 41,45,46 VI, 47 VII, 48,49 and VIII. are rare, 51 although the use of P,N ligands for gold(III) have allowed the synthesis of organogold(III) complexes and mechanistic studies. 52,53 The mechanism of catalysis with phosphorus-containing gold(III) complexes remains virtually unexplored.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold(III)-complexing ligands offering a phosphine coordination site along with an additional heteroatomic electron donor Received: September 11, 2020 Published: November 10, 2020 41 II, 42 III, 42 IV, 43,44 V, 41,45,46 VI, 47 VII, 48,49 and VIII. are rare, 51 although the use of P,N ligands for gold(III) have allowed the synthesis of organogold(III) complexes and mechanistic studies. 52,53 The mechanism of catalysis with phosphorus-containing gold(III) complexes remains virtually unexplored.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Gold­(III)-complexing ligands offering a phosphine coordination site along with an additional heteroatomic electron donor are rare, although the use of P , N ligands for gold­(III) have allowed the synthesis of organogold­(III) complexes and mechanistic studies. , The mechanism of catalysis with phosphorus-containing gold­(III) complexes remains virtually unexplored. Herein, we assess the structure and reactivity of gold­(III) complexes of P , N -donor ligands with solution NMR spectroscopic, X-ray crystallographic, and computational (density functional theory, DFT) techniques.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that most of the d‐block metals may be embedded within the binding pockets of the different pincer scaffolds shown in Scheme and Scheme although there are transition metal that remain to be explored in that context (see Scheme ). It is notably that all the metals that have not yet been coordinated to N ‐heterocyclic PNP pincers, were shown to form alkylamide‐, arylamide‐ or silylamide‐based PNP pincer complexes . It therefore seems likely that for these metals N ‐heterocyclic PNP pincers will also prove to be useful ancillary ligands.…”
Section: Future Directionsmentioning
confidence: 99%
“…[5] More importantly, they are more prone to thermal-or photo-induced decomposition via reductive elimination which can be prevented using chelating ligands. [6] With monodentate ligands, the best stabilities are achieved with aryls, pyridines, imines, dithiocarbamates. [7] Since the beginning of the 2000's, gold chemistry has witnessed a resurgence of interest from the community of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to gold(I) complexes, they clusterize to a lesser extent through metallophilic (d 8 –d 8 ) interactions [5] . More importantly, they are more prone to thermal‐ or photo‐ induced decomposition via reductive elimination which can be prevented using chelating ligands [6] . With monodentate ligands, the best stabilities are achieved with aryls, pyridines, imines, dithiocarbamates [7] …”
Section: Introductionmentioning
confidence: 99%